Employment to output elasticities and reforms towards flexicurity: Evidence from OECD countries - Holger Görg; Cecília Hornok; Catia Montagna; George E. Onwordi (Bulletin of Economic Research, 2022)
Labor market reforms in the direction of “flexicurity” have been widely endorsed as a means to increase an economy's ability to adjust to negative shocks while offering adequate social safety nets. This paper empirically examines how such reforms influence employment's responsiveness to output fluctuations (employment–output elasticity). To address this question, we employ a single equation~error correction model with policy interactions on a panel of OECD countries, which also incorporates the period of the Great Recession, and distinguish between passive and active labor market policy types. Flexicurity is represented by three policy measures: unemployment benefit generosity, the flexibility of hiring and firing rules, and spending on active labor market policies. We find that the effects of any single policy change are shaped by the broader existing policy mix within which it takes place. A hypothetical flexicurity reform towards the policy mix of Denmark, a well-known example of the flexicurity regime, is found to increase or leave unchanged countries' short-run employment–output elasticities, depending on the initial policy mix. These results are robust to accounting for a large set of additional labor market institutions.
Keywords: 330; employment–output elasticity; flexicurity; labor market policy; welfare state